2016
DOI: 10.1055/s-0035-1571147
|View full text |Cite
|
Sign up to set email alerts
|

Tocolysis for Acute Preterm Labor: Where Have We Been, Where Are We Now, and Where are We Going?

Abstract: Tocolytics have been used for over 60 years for women with preterm labor, which ultimately can lead to preterm birth (PTB). Diagnosing preterm labor is challenging, but use of objective tests such as transvaginal ultrasound of cervical length assists in the identification of women at the highest risk for PTB. Once preterm labor has been diagnosed, clinicians can choose from a variety of drug classes (cyclooxygenase inhibitors, calcium channel blockers, and betamimetics) to achieve the primary goal of delaying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 49 publications
0
8
0
18
Order By: Relevance
“…Navathe and Berghella 2016 17 define “true preterm labour” as regular preterm contractions in connection with a cervical length measured transvaginally of < 20 mm or 20 – 29 mm and a positive fibronectin test in the cervicovaginal secretions; in the case of these pregnant women, they see an indication for inpatient admission, tocolysis and induction of foetal lung maturation.…”
Section: Indications For Tocolysismentioning
confidence: 99%
See 4 more Smart Citations
“…Navathe and Berghella 2016 17 define “true preterm labour” as regular preterm contractions in connection with a cervical length measured transvaginally of < 20 mm or 20 – 29 mm and a positive fibronectin test in the cervicovaginal secretions; in the case of these pregnant women, they see an indication for inpatient admission, tocolysis and induction of foetal lung maturation.…”
Section: Indications For Tocolysismentioning
confidence: 99%
“…A possible algorithm for actions to be taken, published by some authors in the meantime 1 , 17 , 18 , 19 , is shown in Fig. 1 .…”
Section: Indications For Tocolysismentioning
confidence: 99%
See 3 more Smart Citations